Social Interaction Among Boys and Girls with Special Educational Needs and Their Peers. A Narrative Review - Arroyo, Gabriela; Toro-Mayorga, Lorena Isabel (Revista Ecos de la Academia, 2021)
At a national and global level, educational environments are increasingly open to inclusion and to the search for a healthier coexistence among students with different ways of learning. This study seeks to analyze the social relationships between boys and girls with Special Educational Needs (SEN) and their peers, using a narrative review as a method of analysis of articles related to the topic. The search strategy for the selected works was performed according to the principles of PRISMA, resulting in a preliminary selection of 21 studies, validated through the Quality Assessment Tool, which finally included 14 studies for the narrative review. Three guiding questions guide the analysis, what are the characteristics of social interaction between boys and girls with SEN and their peers? What are the benefits and limitations that regular education settings offer for children with SEN? And how do peer attitudes relate to learning? The results show that in general, boys and girls with SEN experience exclusion from their peer group; however, with a more particular look in studies with specific variables of age and gender, it is found that girls and early-age students show more positive attitudes towards their peers with SEN. In addition, studies suggest that the mere admission of students with SEN in regular educational environments is not enough to achieve full inclusion, it is necessary a permanent support, interventions and training for teachers and students in schools. Several studies suggest that the family environment and a more tolerant social environment towards diversity are important aspects for the development of positive attitudes towards people with SEN. Finally, the literature analyzed shows a permanent debate regarding whether peer attitudes are positively or negatively related to learning.